Enoxaparin Induced Maculopapular Rash - Varghese, Niphy Annie; Gangadhar, Savitha Tarikere; Menon, Vineetha Bharathan; Undela, Krishna; Ramesh, Madhan (Indian Journal of Pharmacy Practice)
Enoxaparin is the most frequently prescribed low molecular weight heparin worldwide. It has reports of causing rare cutaneous reactions at therapeutic and toxic doses. Herein we report a case of erythematous maculopapular rashes presumed secondary to enoxaparin administration. A 65-year-old male patient diagnosed with acute coronary syndrome developed erythematous maculopapular rashes over the trunk and upper limb after receiving two doses of injection enoxaparin 40 mg. His past medical history was insignificant. The symptoms resolved two days after stopping the drug. Based on his presentation, we presume that the condition was result of enoxaparin. Causality assessment was also suggestive of a probable relationship between the patient’s symptoms and use of enoxaparin.Enoxaparin can cause cutaneous adverse reactions among patients sensitive to this drug. While the pathophysiology of these cutaneous adverse drug reactions is incompletely understood, clinicians should be vigilant to allow early detection of these problems.
Keywords: Cutaneous adverse drug reactions; Drug allergy; Enoxaparin; Geriatric; Low molecular weight heparin; Maculopapular rash